High-nickel positive electrode material as well as preparation method and application thereof

By preparing high-nickel positive electrode materials with a gradient distribution of specific Co content, the problems of unstable structure of high-nickel positive electrode materials and poor cell circulation performance are solved, and the effect of improving the capacity and energy density of lithium-ion batteries is achieved.

CN119542413AActive Publication Date: 2025-02-28NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD

Patent Information

Application Number
CN202411390258.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-28
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The structure of the high-nickel positive electrode material is unstable during the charging and discharging process, resulting in cycling stability and safety problems of lithium-ion batteries. In addition, the active substance will be lost when the residual alkali is removed through the water washing process, affecting the energy density.

Method used

Through a high nickel positive electrode material preparation method, the secondary particle structure formed by primary particles is adopted, and by limiting the gradient distribution of the Co content, the overall Co content of the secondary particles is avoided, the penetration and diffusion of the electrolyte is inhibited, and the structural stability of the material is improved.

Benefits of technology

It improves the gram capacity and energy density of lithium-ion batteries, extends the cycle life of the battery, and enhances the structural stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542413A_ABST
    Figure CN119542413A_ABST
Patent Text Reader

Abstract

The invention provides a high-nickel positive electrode material and a preparation method and application thereof. The high-nickel positive electrode material can effectively control the overall Co content of the secondary particles so as to avoid the situation that the overall Co content of the secondary particles is too high, consequently, the gram volume of a lithium ion battery is reduced, and then the energy density is affected, permeation and diffusion of an electrolyte can be effectively inhibited, corrosion of the electrolyte to the interior of the high-nickel positive electrode material is resisted, and the service life of the high-nickel positive electrode material is prolonged. And the electrolyte is prevented from reacting with active substances in the high-nickel positive electrode material, so that the structural stability of the high-nickel positive electrode material is improved, and the cycle performance of the lithium ion battery is finally improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a high-nickel positive electrode material and a preparation method and application thereof. Background Art

[0002] The rapid growth of the electric vehicle market has led to a growing demand for batteries. High-nickel cathode materials are widely used in lithium-ion batteries due to their high energy density and low cost. However, during the charge and discharge process, these materials can cause structural instability due to the redox reaction of the nickel element, which can affect the battery's cycling stability. Furthermore, the preparation of these materials often produces a large amount of residual alkali, which reacts with the electrolyte, causing capacity decay and safety issues.

[0003] To solve the above problems, a water washing process is usually used to remove residual alkali in high-nickel positive electrode materials, and the structural stability of high-nickel positive electrode materials is improved by doping and coating, thereby reducing their side reactions with the electrolyte. For example, dopants such as Zr, Ti, Al, Y, and Sr are added to improve the structural stability of high-nickel positive electrode materials, and coating agents such as Al, B, Ce, P, F, Cl, and Br are added to reduce the side reactions of high-nickel positive electrode materials with the electrolyte. Although this solves the cyclic stability problem of high-nickel positive electrode materials to a certain extent, there are still some other problems. First, the water washing process can effectively remove residual alkali, but it will lose some active substances, resulting in a decrease in the energy density of the battery. Secondly, although doping and coating can improve the stability of high-nickel positive electrode materials to a certain extent, in actual use, due to the high surface reactivity of high-nickel materials, the penetration and diffusion of the electrolyte can easily lead to a large number of side reactions on the surface of the high-nickel positive electrode materials, resulting in the active substances inside the positive electrode materials not being fully utilized, thereby affecting the cycle performance of the battery. Summary of the Invention

[0004] The present invention provides a high-nickel cathode material, which can increase the gram capacity of a lithium-ion battery, thereby increasing the energy density, and can also improve the structural stability of the high-nickel cathode material, ultimately improving the cycle performance of the lithium-ion battery.

[0005] The present invention provides a preparation method of the above-mentioned high-nickel positive electrode material, which is simple to operate, does not require a water washing process, can effectively remove residual alkali in the high-nickel positive electrode material to avoid the loss of part of the active substance leading to a decrease in the energy density of the battery, and further improves the cycle performance of the high-nickel positive electrode material by improving the sintering and coating conditions. While ensuring the structural stability of the high-nickel positive electrode material, the utilization rate of the active substance inside the secondary particles is increased, thereby improving the cycle performance of the battery.

[0006] The present invention also provides a lithium-ion battery comprising the above-mentioned high-nickel positive electrode material or the high-nickel positive electrode material prepared by the above-mentioned preparation method, which has excellent gram capacity and cycle performance.

[0007] The present invention provides a high-nickel positive electrode material, wherein the high-nickel positive electrode material is secondary particles formed by agglomeration of primary particles, wherein the ratio of the surface Co content of the primary particles located on the surface of the secondary particles to the central Co content is M1; the ratio of the surface Co content of the primary particles located between the surface of the secondary particles and the 1 / 2 of the secondary particle center is M2 to the central Co content; the ratio of the surface Co content of the primary particles located at the center of the secondary particles to the central Co content is M3; M1>M2>M3; M1≥2, M2≥1.5, M3≥1.1.

[0008] The high nickel cathode material as described above, wherein the chemical formula of the high nickel cathode material is Li y Ni a Co b Mn c O2,

[0009] Among them, 0.98≤y≤1.10, 0.6≤a≤0.98, 0≤b≤0.4, 0≤c≤0.4.

[0010] The high nickel cathode material as described above, wherein the chemical formula of the high nickel cathode material is Li y Ni a Co b Mn c A1 d B1 e O2,

[0011] Among them, 0.98≤y≤1.10, 0.6≤a≤0.98, 0≤b≤0.4, 0≤c≤0.4, 1.001≤d≤0.1, 0.001≤e≤0.1;

[0012] A1 is at least one of Zr, Ti, Al, Y, and Sr;

[0013] B1 is at least one of Al, B, Ce, P, F, Cl, and Br.

[0014] As described above, the high nickel positive electrode material, wherein the central Co content of the primary particle located on the surface of the secondary particle is greater than the central Co content of the primary particle located 1 / 2 from the surface of the secondary particle to the center of the secondary particle > the central Co content of the primary particle located at the center of the secondary particle.

[0015] The high nickel cathode material as described above, wherein the average grain size of the primary particles is 150-350 nm;

[0016] and / or, the particle size D50 of the secondary particles is 7.5-12.5 μm;

[0017] And / or, the average particle compressive strength of the secondary particles is 50-200 MPa.

[0018] The high nickel cathode material as described above, wherein the high nickel cathode material is detected by X-ray photoelectron spectroscopy XPS and inductively coupled plasma emission spectroscopy ICP-OES to obtain Co XPS 、Ni XPS 、Co ICP and Ni ICP ;Co XPS 、Ni XPS 、Co ICP and Ni ICP The relationship satisfying formula 1 is:

[0019]

[0020] Among them, Co XPS is the Co content on the surface of secondary particles; Ni XPS is the Ni content on the surface of secondary particles; Co ICP is the total Co content of the secondary particles; Ni ICP is the overall Ni content of the secondary particles;

[0021] And / or, the high nickel positive electrode material obtains a diffraction peak intensity I003 of the (003) plane and a diffraction peak intensity I104 of the (104) plane by X-ray diffraction XRD, and the diffraction peak intensity I003 / I104 satisfies 1.8-3.0.

[0022] The present invention provides a method for preparing the above-mentioned high-nickel positive electrode material, comprising the following steps:

[0023] The precursor Ni a Co b Mn c (OH)2 and a lithium source are mixed and first sintered to obtain a first sintered material, and the first sintered material is crushed to obtain a first crushed material with a particle size D50 of 7.5-12.5 μm;

[0024] The first crushed material and the Co source are mixed and subjected to a second sintering to obtain a high-nickel positive electrode material;

[0025] Among them, 0.6≤a≤0.98, 0≤b≤0.4, 0≤c≤0.4;

[0026] The second sintering temperature is 540-640°C, and the second sintering time satisfies the relationship of formula 2:

[0027]

[0028] Wherein, t is the second sintering time, h; D is the average grain size of the primary particles of the first crushed material, nm; D50 is the particle size D50 of the secondary particles of the first crushed material, μm; T is the second sintering temperature, °C.

[0029] In the preparation method as described above, the first sintering temperature is 750-900° C., and the first sintering time is 8-15 hours.

[0030] The preparation method as described above, wherein the first sintering further comprises the following steps: a Co b Mn c (OH)2, lithium source and Al dopant are mixed;

[0031] The second sintering further includes performing the second sintering to obtain a second sintered material; mixing the second sintered material and the B1 coating agent and performing the third sintering to obtain a high-nickel positive electrode material;

[0032] The Al dopant includes at least one of a Zr source, a Ti source, an Al source, a Y source, and a Sr source;

[0033] The B1 coating agent includes at least one of an Al source, a B source, a Ce source, a P source, a F source, a Cl source, and a Br source;

[0034] The third sintering temperature is 240-340° C., and the third sintering time is 4-15 hours.

[0035] The present invention also provides a lithium-ion battery, comprising the above-mentioned high-nickel positive electrode material or the high-nickel positive electrode material prepared by the above-mentioned preparation method.

[0036] The present invention provides a high-nickel positive electrode material. When the position of the primary particle is closer to the center of the secondary particle, the ratio of the Co content on the surface of the primary particle to the Co content in the center of the primary particle is smaller. The high-nickel positive electrode material can effectively control the Co content of the secondary particles as a whole, so as to avoid excessively high Co content in the secondary particles as a whole, which leads to a decrease in the gram capacity of the lithium-ion battery and thus affects the energy density. The high-nickel positive electrode material can also effectively inhibit the penetration and diffusion of the electrolyte, thereby preventing the active material inside the high-nickel positive electrode material from being fully utilized, thereby improving the structural stability of the high-nickel positive electrode material and ultimately improving the cycle performance of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the overall TEM image of the high nickel cathode material in Example 1;

[0038] Figure 2 This is a local TEM image of the surface of secondary particles in the high-nickel cathode material in Example 1;

[0039] Figure 3This is the EDS distribution diagram of the Zr element located on the surface of the secondary particles in the high-nickel positive electrode material in Example 1;

[0040] Figure 4 This is the EDS distribution diagram of the Al element located on the surface of the secondary particles in the high-nickel positive electrode material in Example 1;

[0041] Figure 5 This is the EDS distribution diagram of the Co element located on the surface of the secondary particles in the high-nickel positive electrode material in Example 1;

[0042] Figure 6 This is a local TEM image of the center of the secondary particle in the high-nickel cathode material in Example 1;

[0043] Figure 7 This is the EDS surface distribution diagram of the Zr element located at the center of the secondary particle in the high-nickel positive electrode material in Example 1;

[0044] Figure 8 This is the EDS surface distribution diagram of the Al element located at the center of the secondary particle in the high-nickel positive electrode material in Example 1;

[0045] Figure 9 This is the EDS surface distribution diagram of the Co element located at the center of the secondary particle in the high-nickel positive electrode material in Example 1. DETAILED DESCRIPTION

[0046] To make the objectives, technical solutions, and advantages of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts shall fall within the scope of protection of the present invention.

[0047] The first aspect of the present invention provides a high-nickel positive electrode material, which is a secondary particle formed by the agglomeration of primary particles, wherein the ratio of the surface Co content of the primary particles located on the surface of the secondary particles to the central Co content is M1; the ratio of the surface Co content of the primary particles located from the surface of the secondary particles to the 1 / 2 of the secondary particle center is M2; the ratio of the surface Co content of the primary particles located at the center of the secondary particles to the central Co content is M3; M1>M2>M3; M1≥2, M2≥1.5, M3≥1.1.

[0048] The high nickel cathode material of the present invention is a secondary particle formed by the agglomeration of primary particles, wherein the primary particle refers to a single small crystal grain. Such a crystal grain generally has a large surface energy and is therefore easily agglomerated due to weak interaction forces to form secondary particles.

[0049] High-nickel cathode materials offer the advantages of high energy density and high capacity in lithium-ion batteries, but they also suffer from issues such as poor cycling stability and low safety. To address these issues, high-nickel cathode materials are typically surface-coated, with cobalt (Co) coating being a common method.

[0050] In the present invention, the M1, M2, and M3 of the high-nickel positive electrode material are limited to satisfy the above relationship, that is, when the position of the primary particle is closer to the center of the secondary particle, the ratio of the Co content on the surface of the primary particle to the Co content in the center of the primary particle is smaller, and the ratio satisfies M1 ≥ 2, M2 ≥ 1.5, and M3 ≥ 1.1. This shows that in the high-nickel positive electrode material of the present invention, Co is more accumulated on the surface of the primary particles and the secondary particles, and less distributed in the bulk phase. Therefore, compared with the positive electrode material in the prior art in which the Co concentration gradient from high to low is presented from the surface to the center of the secondary particles, In comparison, the present invention can more effectively control the Co content of the secondary particles as a whole, so as to avoid the excessively high Co content of the secondary particles as a whole leading to a decrease in the gram capacity of the lithium-ion battery, thereby affecting the energy density; at the same time, through the above-mentioned relationship limitation, it can also effectively inhibit the penetration and diffusion of the electrolyte, resist the corrosion of the electrolyte on the inside of the high-nickel positive electrode material, avoid the reaction between the electrolyte and the active substance inside the high-nickel positive electrode material, thereby improving the stability of the high-nickel positive electrode material, improving the utilization rate of the active substance inside the high-nickel positive electrode material, and ultimately improving the gram capacity and cycle performance of the lithium-ion battery.

[0051] It can be understood that the values ​​of M1, M2, and M3 satisfying M1≥2, M2≥1.5, and M3≥1.1 refer to the primary particles located on the surface of the secondary particles, whose surface Co content is 2 times or more of the central Co content; the primary particles located at 1 / 2 from the surface of the secondary particles to the center of the secondary particles, whose surface Co content is 1.5 times or more of the central Co content; and the primary particles located at the center of the secondary particles, whose surface Co content is 1.1 times or more of the central Co content.

[0052] In one embodiment, the primary particle located on the surface of the secondary particle has a surface Co content of 8.1wt% and a central Co content of 3.4wt%, that is, M1 is 2.4; the primary particle located at 1 / 2 of the distance from the surface of the secondary particle to the center of the secondary particle has a surface Co content of 5.9wt% and a central Co content of 3.1wt%, that is, M2 is 1.9; the primary particle located at the center of the secondary particle has a surface Co content of 3.7wt% and a central Co content of 3.0wt%, that is, M3 is 1.2.

[0053] In an optional embodiment, the chemical formula of the high nickel cathode material is Li y Ni a Co b Mn cO2, where 0.98≤y≤1.10, 0.6≤a≤0.98, 0≤b≤0.4, 0≤c≤0.4.

[0054] By limiting the composition and ratio of high-nickel positive electrode materials, the gram capacity and energy density can be further increased and the structural stability can be improved, thereby improving the cycle performance.

[0055] In another optional embodiment, the chemical formula of the high nickel cathode material is Li y Ni a Co b Mn c A1 d B1 e O2, where 0.98≤y≤1.10, 0.6≤a≤0.98, 0≤b≤0.4, 0≤c≤0.4, 0.001≤d≤0.1, 0.001≤e≤0.1;

[0056] A1 is at least one of Zr, Ti, Al, Y, and Sr;

[0057] B1 is at least one of Al, B, Ce, P, F, Cl, and Br.

[0058] In the present invention, to further improve structural stability and cycle performance, the high-nickel positive electrode material may further include an Al doping element and a B1 coating layer. Using an Al doping element and limiting the Al doping element to be selected from the above-mentioned range allows the Al doping element to be doped into the bulk phase of the positive electrode material, thereby increasing the particle compressive strength of the secondary particles, reducing transition metal mixing and stabilizing the crystal structure, alleviating lattice contraction and expansion of the positive electrode material during charge and discharge, and improving structural stability. Using a B1 coating layer and limiting the B1 coating layer to be selected from the above-mentioned range can protect the surface of the positive electrode material, slowing down side reactions between the electrolyte and the surface of the positive electrode material, and further improving the cycle performance of the lithium-ion battery.

[0059] Therefore, the composition and ratio of the high-nickel positive electrode material are limited to meet the above ranges, and Al doping elements and B1 coating layers can be introduced to further improve the structural stability and thus enhance the cycle performance.

[0060] In a specific embodiment, the central Co content of the primary particle located on the surface of the secondary particle is greater than the central Co content of the primary particle located halfway between the secondary particle surface and the secondary particle center.

[0061] The positive electrode material obtained by the present invention through the above-mentioned limitations has a lower Co content in the center of the primary particle the closer the position of the primary particle is to the center of the secondary particle. This not only further controls the Co content of the secondary particles as a whole, thereby preventing excessively high Co content in the secondary particles from causing a decrease in the gram capacity of the lithium-ion battery, thereby affecting the energy density; it also further inhibits the penetration and diffusion of the electrolyte, resisting the electrolyte's erosion of the interior of the high-nickel positive electrode material, and preventing the electrolyte from reacting with the active material inside the high-nickel positive electrode material, thereby improving the structural stability of the high-nickel positive electrode material and increasing the utilization rate of the active material inside the high-nickel positive electrode material, ultimately improving the gram capacity and cycle performance of the lithium-ion battery.

[0062] In the solution of the present invention, the average grain size of the primary particles is 150-350 nm;

[0063] and / or, the particle size D50 of the secondary particles is 7.5-12.5 μm;

[0064] And / or, the average particle compressive strength of the secondary particles is 50-200 MPa.

[0065] In high-nickel positive electrode materials, if the average grain size of the primary particles is too large, the lithium ion transmission rate will be too slow, affecting the cycle performance; if the average grain size of the primary particles is too small, it will lead to insufficient sintering of the material, low gram capacity, and low compressive strength of the material particles, and a large BET specific surface area, affecting the cycle performance. Therefore, the present invention limits the average grain size of the primary particles to meet the above range, which can effectively balance the energy density and cycle performance of the high-nickel positive electrode material.

[0066] In high-nickel positive electrode materials, if the particle size D50 of the secondary particles is too large, the lithium ions inside the material will not be fully released, affecting the specific capacity; if the particle size of the secondary particles is too small, the BET specific surface area will be too large, affecting the cycle performance. Therefore, the present invention limits the particle size D50 of the secondary particles to meet the above range, which can balance the energy density and cycle performance of the high-nickel positive electrode material.

[0067] In addition, limiting the average particle compressive strength of the secondary particles to meet the above range helps to further improve the structural stability of the high-nickel positive electrode material and thus improve the cycle performance.

[0068] In the scheme of the present invention, the high nickel cathode material is detected by X-ray photoelectron spectroscopy XPS and inductively coupled plasma emission spectroscopy ICP-OES to obtain Co XPS 、Ni XPS 、Co ICP and Ni ICP ;Co XPS 、Ni XPS 、Co ICP and Ni ICPThe relationship satisfying formula 1 is:

[0069]

[0070] Among them, Co XPS is the Co content on the surface of secondary particles; Ni XPS is the Ni content on the surface of secondary particles; Co ICP is the total Co content of the secondary particles; Ni ICP is the overall Ni content of the secondary particles;

[0071] And / or, the high nickel positive electrode material obtains a diffraction peak intensity I003 of the (003) plane and a diffraction peak intensity I104 of the (104) plane by X-ray diffraction XRD, and the diffraction peak intensity I003 / I104 satisfies 1.8-3.0.

[0072] X-ray photoelectron spectroscopy (XPS) is a technique that uses an electron spectrometer to measure the energy distribution of photoelectrons and Auger electrons emitted from the sample surface when irradiated by X-ray photons. It can be used for qualitative analysis and semi-quantitative analysis. It can obtain information such as the elemental composition, chemical state and molecular structure of the sample surface from the peak position and peak shape of the XPS spectrum, and obtain the element content or concentration of the sample surface from the peak intensity. Therefore, the high nickel cathode material of the present invention can be tested by XPS to obtain Co XPS , represents the Co content on the surface of secondary particles, the unit is wt%; similarly, Ni XPS , represents the Ni content on the surface of secondary particles, the unit is wt%.

[0073] Inductively coupled plasma optical emission spectrometry (ICP-OES) is a technique for atomic emission spectrometry using a light source that generates plasma discharge through high-frequency inductive coupling. It is a flame technique with a flame temperature range of 6000 to 10000K. The emission intensity represents the concentration of elements in the sample. Therefore, the high nickel cathode material of the present invention can be tested by ICP-OES to obtain Co ICP , represents the total Co content of the secondary particles, the unit is wt%; similarly, Ni can also be obtained by ICP-OES detection. ICP , represents the total Ni content of the secondary particles, the unit is wt%.

[0074] When the Co of the high nickel cathode material of the present invention XPS 、Ni XPS 、Co ICP and Ni ICPWhen the relationship of formula 1 is satisfied, it indicates that the contents of Co and Ni in the high-nickel positive electrode material have a good matching effect, and the Co coating effect on the surface of the secondary particles is good, thereby being able to effectively inhibit the penetration and diffusion of the electrolyte, thereby improving the interface stability of the high-nickel positive electrode material and improving the cycle performance of the lithium-ion battery.

[0075] In addition, the Miller index is an index used to determine the crystal direction, also known as the crystal plane index. The present invention can obtain the diffraction peak intensity I003 of the (003) plane and the diffraction peak intensity I104 of the (104) plane in the Miller index of the high nickel positive electrode material through X-ray diffraction (XRD). I003 / I104 can reflect the Li + / Ni 2+ The degree of cation mixing, limiting this value to the above range, helps to further reduce transition metal mixing and thus improve cycle performance.

[0076] A second aspect of the present invention provides a method for preparing the above-mentioned high-nickel positive electrode material, comprising the following steps:

[0077] The precursor Ni a Co b Mn c (OH)2 and a lithium source are mixed and first sintered to obtain a first sintered material, and the first sintered material is crushed to obtain a first crushed material with a particle size D50 of 7.5-12.5 μm;

[0078] The first crushed material and the Co source are mixed and subjected to a second sintering to obtain a high-nickel positive electrode material;

[0079] Among them, 0.6≤a≤0.98, 0≤b≤0.4, 0≤c≤0.4;

[0080] The second sintering temperature is 540-640°C, and the second sintering time satisfies the relationship of formula 2:

[0081]

[0082] Wherein, t is the second sintering time, h; D is the average grain size of the primary particles of the first crushed material, nm; D50 is the particle size D50 of the secondary particles of the first crushed material, μm; T is the second sintering temperature, °C.

[0083] The preparation method of the present invention is simple to operate and does not require a water washing process. The introduction of a Co source can effectively remove the residual alkali in the high-nickel positive electrode material to avoid the loss of some active substances leading to a decrease in the energy density of the battery. By improving the sintering conditions, a high-nickel positive electrode material with a specific Co concentration gradient is obtained, which further improves the cycle performance of the high-nickel positive electrode material. While ensuring the structural stability of the high-nickel positive electrode material, the utilization rate of the active substances inside the secondary particles is increased, thereby improving the cycle performance of the battery. First, the precursor Ni a Co b Mn c (OH)2 and a lithium source are mixed and subjected to a first sintering to obtain a first sintered material, and then the first sintered material is crushed and the D50 range is controlled to obtain a first crushed material, and then the first crushed material is mixed with a Co source and subjected to a second sintering to obtain a high-nickel positive electrode material. The above steps help to control the overall Co content of the secondary particles to increase the gram capacity and energy density of the lithium-ion battery, and inhibit the penetration and diffusion of the electrolyte to improve the structural stability of the high-nickel positive electrode material to improve the cycle performance of the lithium-ion battery.

[0084] In the present invention, the lithium source may be at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium oxalate, lithium acetate, lithium oxide, and lithium citrate.

[0085] In order to more accurately regulate the high nickel cathode material to improve its energy density and cycle performance, the precursor Ni a Co b Mn c (OH)2 and lithium source are mixed in a molar ratio of 1: (1.010-1.090). At the same time, in order to make the mixing more complete, the precursor Ni a Co b Mn c (OH)2 and lithium source are added into a high-speed mixer for mixing. The mixing speed can be 500 rpm and the mixing time can be 60 min.

[0086] After the precursor and the lithium source are fully mixed, the first sintering is performed. The precursor will undergo a solid-phase lithium insertion reaction during the first sintering to obtain a first sintered material. The first sintering has a key influence on the crystal structure of the high-nickel positive electrode material.

[0087] The first sintering atmosphere can be oxygen or air. To further improve the sintering efficiency, a mixed gas with an oxygen concentration of ≥80% and the remaining gas being air can be selected.

[0088] After the first sintering, the first sintered material is obtained. To facilitate subsequent operations and strengthen the control of high-nickel positive electrode material parameters, the first sintered material needs to be crushed and the D50 is controlled at 7.5-12.5 μm to obtain the first crushed material, and the first crushed material is used for subsequent experiments.

[0089] Next, to further precisely control the high-nickel cathode material to improve its energy density and cycle performance, the first crushed material and the Co source can be mixed at a molar ratio of 1:(0.001-0.100), wherein the cobalt source can be at least one of cobalt tetroxide, cobalt carbonate, cobalt hydroxide, cobalt oxyhydroxide, cobalt acetate, cobalt oxalate, cobalt nitrate, cobalt sulfate, and cobalt chloride. At the same time, to ensure more thorough mixing, the first crushed material and the Co source can be added to a high-speed mixer for mixing at a mixing speed of 500 rpm and a mixing time of 60 minutes.

[0090] After the first crushed material and the Co source are fully mixed, a second sintering is required within a limited temperature and time range. At this time, the Co source will react with the first crushed material and penetrate into the material, thereby obtaining a high-nickel positive electrode material with a specific Co concentration gradient of the present invention.

[0091] During long-term research, the inventors discovered that the temperature and time of the second sintering process have a critical impact on whether the high-nickel cathode material provided by the first aspect of the present invention can be obtained. The present invention first limits the second sintering temperature to 540-640°C. If the second sintering temperature is too low, Co is primarily coated on the surface of the secondary particles. If the second sintering temperature is too high, Co tends to be evenly distributed in the bulk of the high-nickel cathode material. Only when the second sintering temperature meets the above limitations can a good foundation be laid for the specific gradient distribution of Co. After limiting the second sintering temperature, the present invention limits the second sintering time to satisfy the relationship of Formula 2, that is, the second sintering time is adjusted according to the second sintering temperature, the average grain size of the primary particles of the first crushed material and the particle size D50 of the secondary particles of the first crushed material. This can promote a good matching effect between the second sintering time and the second sintering temperature, the average grain size of the primary particles of the first crushed material and the particle size D50 of the secondary particles of the first crushed material, and finally obtain the high-nickel positive electrode material provided by the first aspect of the present invention. In this high-nickel positive electrode material, the closer the position of the primary particle is to the center of the secondary particle, the smaller the ratio of the Co content on the surface of the primary particle to the Co content in the center of the primary particle.

[0092] It can be understood that the high nickel positive electrode material obtained by mixing the first crushed material and the Co source for the second sintering of the present invention has an average grain size of primary particles and a particle size D50 of secondary particles that are basically equivalent to the average grain size of the first crushed material and the particle size D50 of the secondary particles.

[0093] In addition, the atmosphere of the second sintering can be oxygen or air. To further improve the sintering efficiency, a mixed gas with an oxygen concentration of ≥80% and the remaining gas being air can be selected.

[0094] In the solution of the present invention, the first sintering temperature is 750-900°C, and the first sintering time is 8-15 hours. As mentioned above, the first sintering has a key impact on the crystal structure of the high-nickel positive electrode material. Therefore, regulating the first sintering temperature and the first sintering time within the above ranges can obtain a suitable crystal structure, which in turn helps to improve the cycle performance of the battery to a certain extent and significantly increase the specific capacity.

[0095] In a specific embodiment, the first sintering step further includes: a Co b Mn c (OH)2, lithium source and Al dopant are mixed;

[0096] The second sintering further includes performing the second sintering to obtain a second sintered material; mixing the second sintered material and the B1 coating agent and performing the third sintering to obtain a high-nickel positive electrode material;

[0097] The Al dopant includes at least one of a Zr source, a Ti source, an Al source, a Y source, and a Sr source;

[0098] The B1 coating agent includes at least one of an Al source, a B source, a Ce source, a P source, a F source, a Cl source, and a Br source;

[0099] The third sintering temperature is 240-340° C., and the third sintering time is 4-15 hours.

[0100] In the present invention, the precursor Ni can also be a Co b Mn c (OH)2, a lithium source, and an Al dopant are mixed, and after the second sintering, the second sintered material is mixed with a B1 coating agent and subjected to a third sintering, ultimately producing a high-nickel cathode material. By limiting the types of the Al dopant and B1 coating agent, as well as the temperature and time of the third sintering, the present invention can effectively improve the structural stability of the high-nickel cathode material and the cycling performance of lithium-ion batteries.

[0101] First, the precursor Ni a Co b Mn c (OH)2, lithium source and Al dopant are mixed and then sintered for the first time. At this time, Al dopant is doped into the bulk phase of the positive electrode material, thereby improving the particle compressive strength of the secondary particles, reducing the transition metal mixing and stabilizing the crystal structure, and alleviating the lattice shrinkage and expansion of the positive electrode material during charging and discharging. Among the Al dopant, the Zr source, Ti source, Al source, Y source, and Sr source can be at least one of oxides, hydroxides, oxyhydroxides, acetates, oxalates, nitrates, sulfates, and chlorides. In addition, the precursor Ni a Co b Mnc (OH)2, lithium source and Al dopant can be mixed in a molar ratio of 1:(0.980-1.100):(0.001-0.100), which helps to better control the performance of high nickel positive electrode materials.

[0102] Secondly, after the second sintering process to obtain the second sintered material, the second sintered material and the B1 coating agent are mixed and subjected to the third sintering process. By limiting the type of B1 coating agent and the temperature and time of the third sintering process, the B1 coating agent can play a protective role on the surface of the positive electrode material, slowing down the side reactions between the electrolyte and the surface of the positive electrode material, and further improving the cycle performance of the lithium-ion battery. In the B1 coating agent, the Al source, B source, Ce source, P source, F source, Cl source, and Br source can be at least one of their oxides, hydroxides, oxyhydroxides, acetates, oxalates, nitrates, sulfates, and chlorides. In addition, the second sintered material and the B1 coating agent are mixed in a molar ratio of 1: (0.001-0.100), which helps to better control the performance of the high-nickel positive electrode material.

[0103] A third aspect of the present invention provides a lithium-ion battery, comprising the above-mentioned high-nickel positive electrode material or the high-nickel positive electrode material prepared by the above-mentioned preparation method.

[0104] The lithium-ion battery of the present invention includes a positive electrode sheet, which can be prepared using conventional technical means in the field. Specifically, the above-mentioned positive electrode material, conductive agent, and binder can be uniformly dispersed in a solvent to obtain a positive electrode active layer slurry, and then the positive electrode active layer slurry is coated on at least one functional surface of the positive electrode current collector. After drying, the positive electrode sheet can be obtained.

[0105] The lithium-ion battery of the present invention includes, in addition to a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. The composition of the negative electrode sheet can refer to conventional negative electrode sheets in the art, and the separator can also be a separator conventionally used in the art. The lithium-ion battery of the present invention can be prepared using conventional methods in the art. Specifically, the positive electrode sheet, separator, and negative electrode sheet can be stacked in sequence, and then a battery cell can be obtained through a lamination or winding process. The battery can then be obtained through baking, liquid injection, formation, packaging, and other processes.

[0106] The present invention is further described below by way of specific examples and comparative examples. Unless otherwise specified, the reagents, materials, and instruments used below are all conventional reagents, materials, and instruments, all of which are commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.

[0107] Example 1:

[0108] This embodiment provides a method for preparing a high-nickel positive electrode material, comprising the following steps:

[0109] (1) Ni 0.85 Co 0.05 Mn 0.10 (OH)2, lithium source LiOH·H2O, Al dopant ZrO2, and Al2O3 were mixed in a molar ratio of 1:1.050:0.020:0.010 and added to a high-speed mixer for mixing at a speed of 500 rpm for 60 minutes. The mixed material was placed in a sagger and subjected to a first sintering process in a kiln at a temperature of 820°C for 12 hours in an oxygen atmosphere (oxygen concentration ≥80%, with the remainder being air) to obtain a first sintered material. The first sintered material was crushed with a D50 value controlled to be between 9.5 and 10.5 μm to obtain a first crushed material.

[0110] (2) The first crushed material and the Co coating agent Co(OH)2 were mixed in a molar ratio of 1:0.015, and added to a high-speed mixer for mixing at a mixing speed of 500 rpm for 60 min. The mixed material was placed in a sagger and subjected to a second sintering in a kiln at a second sintering temperature of 590°C, a second sintering time of t, and an oxygen atmosphere (oxygen concentration ≥ 80%, the rest being air) to obtain a second sintered material;

[0111] The value of t is shown in formula 1:

[0112]

[0113] Wherein, t is the second sintering time, h; D is the average grain size of the primary particles of the first crushed material, nm; D50 is the particle size D50 of the secondary particles of the first crushed material, μm; T is the second sintering temperature, °C.

[0114] (3) The second sintered material, B1 coating agent A1F3 and H3BO3 were mixed in a molar ratio of 1:0.010:0.010 and added to a high-speed mixer for mixing at a mixing speed of 500 rpm for 60 min. The mixed material was placed in a sagger and subjected to a third sintering in a kiln at a third sintering temperature of 290°C, a third sintering time of 6 h, and an oxygen atmosphere (oxygen concentration ≥80%, the rest being air) to obtain a third sintered material, which was then screened, deironed, and packaged to obtain a high-nickel positive electrode material.

[0115] Example 2:

[0116] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (1) of this embodiment, the Al dopant is TiO2 and Y2O3.

[0117] Example 3:

[0118] This embodiment provides a method for preparing a high nickel positive electrode material. The specific steps can refer to Example 1, the only difference is that in step (1) of this embodiment, the precursor Ni 0.85 Co 0.05 Mn 0.10 (OH)2 and lithium source LiOH·H2O were mixed in a molar ratio of 1:1.050, that is, no Al dopant was added.

[0119] Example 4:

[0120] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (1) of this embodiment, the first sintered material is crushed and the D50 is controlled to be 7.5-8.5 μm.

[0121] Example 5:

[0122] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (1) of this embodiment, the first sintered material is crushed and the D50 is controlled to be 11.5-12.5 μm.

[0123] Example 6:

[0124] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (2) of this embodiment, the second sintering temperature is 540° C. and the second sintering atmosphere is air.

[0125] Example 7:

[0126] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (2) of this embodiment, the second sintering temperature is 640°C, and the second sintering atmosphere is oxygen (oxygen concentration ≥90%, the rest is air).

[0127] Example 8:

[0128] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (2) of this embodiment, the second sintering temperature is 590° C. and the second sintering atmosphere is air.

[0129] Example 9:

[0130] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (3) of this embodiment, the B1 coating agent is CeF3 and NH4H2PO4.

[0131] Example 10:

[0132] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can be referred to in Example 1, with the only difference being steps (2) and (3). In step (2) of this embodiment, the first crushed material and the Co coating agent Co(OH)2 are mixed in a molar ratio of 1:0.020; in step (3) of this embodiment, the second sintered material is directly screened, iron-removed, and packaged to obtain the high-nickel positive electrode material, i.e., no B1 coating agent is added.

[0133] Example 11:

[0134] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (3) of this embodiment, the third sintering time is 20 hours.

[0135] Example 12:

[0136] This embodiment provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (1) of this embodiment, the first sintering temperature is 740°C.

[0137] Comparative Example 1:

[0138] This comparative example provides a method for preparing a high-nickel positive electrode material. The specific steps can be referred to Example 1, except that this comparative example does not perform step (2), but directly mixes the first crushed material with the B1 coating agent A1F3 and H3BO3 in a molar ratio of 1:0.015:0.015.

[0139] Comparative Example 2:

[0140] This comparative example provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (2) of this comparative example, the second sintering temperature is 520°C and the second sintering atmosphere is oxygen (oxygen concentration ≥90%, the rest is air).

[0141] Comparative Example 3:

[0142] This comparative example provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1, with the only difference being that in step (2) of this comparative example, the second sintering temperature is 660° C. and the second sintering atmosphere is air.

[0143] Comparative Example 4:

[0144] This comparative example provides a method for preparing a high-nickel positive electrode material. The specific steps can refer to Example 1. The only difference is that in step (2) of this comparative example, the second sintering time is t+1h, that is, the second sintering time is always 1 hour longer than the sintering time in step (2) of Example 1.

[0145] Test example:

[0146] (1) Using Bruker's X-ray diffraction (XRD) test, specifically using Cu Kα ray to perform powder X-ray diffraction test, to detect the average grain size of the primary particles of the first crushed material in the above embodiment and the above comparative example; using Malvern's laser particle size analyzer to detect the particle size D50 of the secondary particles of the first crushed material in the above embodiment and the above comparative example; using Shimadzu's micro compression testing machine to detect the average particle compressive strength of the secondary particles of the high nickel positive electrode material in the above embodiment and the above comparative example, at least 10 particles with a particle size D50 were tested for each sample, and the results were averaged; using Shimadzu's X-ray photoelectron spectrometer (XPS) to detect the weight percentage of Co on the surface of the high nickel positive electrode material in the above embodiment and the above comparative example to obtain Co XPS , and the weight percentage of Ni on the surface of the high nickel cathode material to obtain Ni XPS , wherein the quantitative calculation adopts the Wagner experimental sensitivity factor; the overall Co content of the high nickel positive electrode material in the above embodiment and the above comparative example is detected by inductively coupled plasma optical emission spectrometry (ICP-OES) to obtain Co ICP , and the overall Ni content to obtain Ni ICP ; Bruker's XRD test, specifically Cu Kα ray powder X-ray diffraction test, was used to detect the diffraction peak intensity I003 of the (003) plane and the diffraction peak intensity I104 of the (104) plane of the high nickel positive electrode material in the above embodiment and the above comparative example. The specific results can be seen in Table 1, wherein, according to Co XPS 、Ni XPS 、Co ICP and Ni ICP The M value can be obtained, and the M value is calculated by the following relationship:

[0147]

[0148] (2) The high nickel cathode material in the above embodiment and the above comparative example, in which the particle size D50 of the secondary particles of the first crushed material meets the range of 7.5-12.5 μm, was sliced ​​using a focused ion beam (FIB) to obtain slices with a thickness of 50-100 nm. The slices were then subjected to point scanning by transmission electron microscopy energy dispersive X-ray spectroscopy (TEM-EDS) to obtain the content of each element on the surface and in the center of the primary particles. The specific results are shown in Tables 2 and Figure 1-9 shown.

[0149] (3) The high nickel positive electrode material in the above embodiment and the above comparative example is mixed with the conductive agent conductive carbon black (Super-P) and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 94.5:3:2.5, and an appropriate amount of N-methylpyrrolidone (NMP) solution is added to form a slurry. The slurry is then coated on a positive electrode sheet made of aluminum foil, dried, and baked in a vacuum oven at 120°C for 12 hours. After completion, the positive electrode sheet is assembled with an artificial graphite negative electrode sheet, a PP / PE / PP composite separator, and an electrolyte of 1.0MLiPF6 / ethylene carbonate (EC) + dimethyl carbonate (DMC) + ethyl methyl carbonate (EMC) to obtain an 800mAh soft pack battery, wherein the volume ratio of EC:DMC:EMC is 1:1:1. The gram capacity and 300-cycle retention rate of the above-mentioned soft-pack battery were tested, wherein the 300-cycle test conditions were 25°C, 2.8-4.25V, 1C. The specific results are shown in Table 2.

[0150] Table 1

[0151]

[0152]

[0153] Table 2

[0154]

[0155] As shown in Tables 1 and 2, compared with Example 1, the Al dopant used in Example 2 was replaced with TiO2 and Y2O3, and it was found that it had no significant effect on the battery capacity and cycle performance; compared with Example 1, Example 3 did not add Al dopant, and it was found that the average particle compressive strength and I003 / I104 of its secondary particles were extremely low, and its 300-cycle retention rate was worse than that of Example 1 and Example 2, indicating that the Al dopant can improve the cycle performance; in Example 1, the D50 of the first crushed material was 9.5-10.5 μm, and in Example 4, the D50 of the first crushed material was 50 is 7.5-8.5μm, and the first crushed material D50 in Example 5 is 11.5-12.5μm. It can be found that when the first crushed material D50 is 7.5-12.5μm, the battery gram capacity and cycle performance obtained are better; the first sintering temperature of Example 1 is 590℃ and the second sintering atmosphere is mainly oxygen, the second sintering temperature of Example 6 is 540℃ and the second sintering atmosphere is air, the second sintering temperature of Example 7 is 640℃ and the second sintering atmosphere is mainly oxygen, the second sintering temperature of Example 8 is 590℃ and the second sintering atmosphere is mainly oxygen. For air, it can be found that when the second sintering temperature is in the range of 540-640℃, the battery gram capacity and cycle performance are good; compared with Example 1, the B1 coating agent used in Example 9 is replaced with CeF3 and NH4H2PO4, and it can be found that it has no significant effect on the battery gram capacity and cycle performance; in Example 10, no B1 coating agent is added, and it can be found that the average particle compressive strength of its secondary particles is low, the M value is high, its gram capacity is reduced, and the 300-cycle cycle retention rate is significantly worse than that of Example 1 and Example 9, indicating that the B1 coating agent can significantly improve the battery gram capacity and cycle performance. The third sintering time of Example 11 is 20h, and its 300-cycle cycle retention rate is significantly worse than that of Example 1 and Example 9, indicating that when the third sintering time exceeds 15h, the cycle performance of the obtained battery will be reduced; the first sintering temperature of Example 12 is 740℃, and the average particle compressive strength and I003 / I104 of its secondary particles are extremely low, its gram capacity is significantly reduced, and the 300-cycle cycle retention rate also decreases to a certain extent, indicating that the first sintering temperature is too high, which can easily lead to a significant reduction in the battery's gram capacity.

[0156] Comparative Example 1 does not perform step (2), and the resulting high-nickel positive electrode material has a low surface Co content of the primary particles located on the surface of the secondary particles, while the Co content of the remaining positions is basically the same. Its M value is extremely significantly reduced, and the 300-cycle cycle retention rate is significantly reduced, indicating that step (2) of the present invention, i.e., the second sintering, plays an extremely important role in obtaining the high-nickel positive electrode material of the present invention having a specific Co concentration gradient and a balance between gram capacity and cycle performance. The second sintering temperature of Comparative Example 2 is 520°C and the second sintering atmosphere is mainly oxygen. It can be found that the M2 of Comparative Example 2 is about 1.3, while M3 is about 1.0, indicating that more Co is accumulated on the surface of the secondary particles, which is not conducive to the formation of a Co concentration gradient and cannot effectively improve the cycle performance. The second sintering temperature of Comparative Example 3 is 660°C and the second sintering atmosphere is air. It can be found that the M value of Comparative Example 3 is significantly reduced, and Co is more evenly distributed in the secondary particle phase, which is not conducive to the formation of a Co concentration gradient and cannot effectively improve the cycle performance. The second sintering time of Comparative Example 4 is 1 hour longer than that of Example 1, that is, it does not satisfy the value relationship of Formula 1. It can be found that M1 of Comparative Example 4 is about 1.8, while M2 is about 1.4, indicating that the distribution of Co tends to be uniform, which is not conducive to the formation of a special Co-rich structure on the surface of the primary particles. Its 300-cycle cycle retention rate is significantly reduced, which shows that controlling the time of the second sintering plays an important role in improving the cycle performance.

[0157] Figure 1 This is the overall TEM image of the high-nickel positive electrode material in Example 1. It can be found that the high-nickel positive electrode material of the present invention is secondary particles formed by the agglomeration of primary particles.

[0158] Figure 2 This is a local TEM image of the surface of secondary particles in the high nickel cathode material in Example 1. Figure 3 This is the EDS distribution diagram of the Zr element located on the surface of the secondary particles in the high nickel positive electrode material in Example 1. Figure 4 This is the EDS distribution diagram of the Al element on the surface of the secondary particles in the high nickel positive electrode material in Example 1. Figure 5 This is the EDS distribution diagram of the Co element on the surface of the secondary particles in the high nickel positive electrode material in Example 1. Figure 1-5 It can be found that on the surface of the secondary particles, the Zr and Al elements are distributed relatively evenly, indicating that the Al dopant is uniformly doped; while on the primary particles located on the surface of the secondary particles, the surface Co element and the central Co element have obvious concentration gradients, and more Co elements are evenly coated on the surface of the primary particles.

[0159] Figure 6 This is a local TEM image of the center of the secondary particle in the high nickel cathode material in Example 1. Figure 7 This is the EDS surface distribution diagram of the Zr element located at the center of the secondary particle in the high-nickel positive electrode material in Example 1. Figure 8This is the EDS surface distribution diagram of the Al element located at the center of the secondary particle in the high nickel positive electrode material in Example 1. Figure 9 This is the EDS distribution diagram of the Co element located at the center of the secondary particle in the high nickel positive electrode material in Example 1. Figure 6-9 It can be found that at the center of the secondary particle, the Zr and Al elements are still distributed relatively evenly, indicating that the Al dopant is still evenly doped at the center of the sphere; while the primary particle located at the center of the secondary particle has a more obvious concentration gradient of Co element on its surface and in the center, and more Co element is evenly coated on the surface of the primary particle.

[0160] In addition, comparison Figure 5 and Figure 9 It can be found that the surface Co element of the primary particles located on the surface of the secondary particles is significantly higher than the surface Co element of the primary particles located at the center of the secondary particles. At the same time, the central Co element of the primary particles located on the surface of the secondary particles is significantly higher than the central Co element of the primary particles located at the center of the secondary particles.

[0161] The above describes in detail the preferred embodiments of the present invention and their experimental verification. It should be understood that a person skilled in the art can make numerous modifications and variations based on the concepts of the present invention without inventive effort. Therefore, any technical solution that can be derived by a person skilled in the art through logical analysis, reasoning, or limited experimentation based on the concepts of the present invention and the prior art shall be within the scope of protection of the present invention.

Claims

1. A high nickel positive electrode material, characterized in that: The high-nickel positive electrode material is a secondary particle formed by the agglomeration of primary particles, wherein the ratio of the surface Co content to the central Co content of the primary particle located on the surface of the secondary particle is M1; the ratio of the surface Co content to the central Co content of the primary particle located at 1 / 2 of the secondary particle surface to the center of the secondary particle is M2; the ratio of the surface Co content to the central Co content of the primary particle located at the center of the secondary particle is M3; M1>M2>M3; M1≥2, M2≥1.5, and M3≥1.

1.

2. The high nickel positive electrode material according to claim 1, characterized in that: The chemical formula of the high nickel cathode material is Li y Ni a Co b Mn c O2, Among them, 0.98≤y≤1.10, 0.6≤a≤0.98, 0≤b≤0.4, 0≤c≤0.

4.

3. The high nickel positive electrode material according to claim 1, characterized in that: The chemical formula of the high nickel cathode material is Li y Ni a Co b Mn c A1 d B1 e O2, Among them, 0.98≤y≤1.10, 0.6≤a≤0.98, 0≤b≤0.4, 0≤c≤0.4, 0.001≤d≤0.1, 0.001≤e≤0.1; A1 is at least one of Zr, Ti, Al, Y and Sr; B1 is at least one of Al, B, Ce, P, F, Cl, and Br.

4. The high nickel positive electrode material according to any one of claims 1 to 3, characterized in that: The central Co content of the primary particle located on the surface of the secondary particle>the central Co content of the primary particle located halfway from the surface of the secondary particle to the center of the secondary particle>the central Co content of the primary particle located at the center of the secondary particle.

5. The high nickel positive electrode material according to any one of claims 1 to 4, characterized in that: The average grain size of the primary particles is 150-350 nm; and / or, the particle size D50 of the secondary particles is 7.5-12.5 μm; And / or, the average particle compressive strength of the secondary particles is 50-200 MPa.

6. The high nickel positive electrode material according to any one of claims 1 to 5, characterized in that: The high nickel positive electrode material is detected by X-ray photoelectron spectroscopy XPS and inductively coupled plasma emission spectroscopy ICP-OES to obtain Co XPS 、Ni XPS 、Co ICP and Ni ICP ; The Co XPS 、Ni XPS 、Co ICP and Ni ICP The relationship satisfying equation 1 is: Wherein, the Co XPS is the Co content on the surface of the secondary particles; the Ni XPS is the Ni content on the secondary particle surface; ICP is the total Co content of the secondary particles; the Ni ICP is the overall Ni content of the secondary particles; And / or, the high-nickel positive electrode material obtains a diffraction peak intensity I003 of the (003) plane and a diffraction peak intensity I104 of the (104) plane through X-ray diffraction XRD, and the diffraction peak intensity I003 / I104 is 1.8-3.

0.

7. A method for preparing the high-nickel positive electrode material according to any one of claims 1 to 6, characterized in that: The steps include: The precursor Ni a Co b Mn c (OH)2 and a lithium source are mixed and first sintered to obtain a first sintered material, and the first sintered material is crushed to obtain a first crushed material with a particle size D50 of 7.5-12.5 μm; The first crushed material and the Co source are mixed and subjected to a second sintering to obtain the high-nickel positive electrode material; Among them, 0.6≤a≤0.98, 0≤b≤0.4, 0≤c≤0.4; The second sintering temperature is 540-640° C., and the second sintering time satisfies the relationship of formula 2: Wherein, t is the second sintering time, h; D is the average grain size of the primary particles of the first crushed material, nm; D50 is the particle size D50 of the secondary particles of the first crushed material, μm; T is the second sintering temperature, °C.

8. The preparation method according to claim 7, characterized in that: The first sintering temperature is 750-900° C., and the first sintering time is 8-15 hours.

9. The preparation method according to claim 7 or 8, characterized in that: The first sintering step also includes: a Co b Mn c (OH)2, lithium source and Al dopant are mixed; The second sintering further includes obtaining a second sintering material after the second sintering; mixing the second sintering material and the B1 coating agent for a third sintering to obtain the high-nickel positive electrode material; The Al dopant includes at least one of a Zr source, a Ti source, an Al source, a Y source, and a Sr source; The B1 coating agent includes at least one of an Al source, a B source, a Ce source, a P source, a F source, a Cl source, and a Br source; The third sintering temperature is 240-340° C., and the third sintering time is 4-15 hours.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the high-nickel positive electrode material according to any one of claims 1 to 8 or the high-nickel positive electrode material prepared by the preparation method according to claim 9.

Citation Information

Patent Citations

  • Positive electrode active material, nonaqueous electrolyte battery and method for manufacturing positive electrode active material

    CN102315447A

  • Agglomeration-like multi-element positive electrode material, preparation method and application thereof, and lithium ion battery

    CN116111081A

  • High-nickel positive electrode material as well as preparation method and application thereof

    CN117525386A

  • High-nickel positive electrode material as well as preparation method and application thereof

    CN117712371A

  • Positive electrode active material for rechargeable lithium ion battery

    CN117836243A

Cited By

  • Positive electrode active material powder

    WO2026209640A1